Effect of Biased Neighboring Wire on Polysilicon Wire Biosensors with Sensing Membrane of γ-APTES Mixed with Polydimethylsiloxane-Treated Silica Nanoparticles. (15th February 2021) - Liao, Su-Yu; Lin, Jing-Jenn; Ching, Congo Tak-Shing; Wu, You-Lin
Abstract : Voltages simultaneously applied to two adjacent nanoscale sensors in sensor array might cause false readings. In this work, we investigated the interference effect resultant from a biased neighboring wire on the pH sensing characteristics of the polysilicon wire (PSW) sensors array with sensing membranes of 3-aminopropyltrimethylsiloxane ( γ -APTES) and polydimethylsiloxane (PDMS)-treated silica nanoparticles (NPs) plus UV light exposure ( γ -APTES + NPs + UV). The current-voltage (I–V) characteristics of the PSW sensors were used to measure the buffer solutions with different pH values under the influences of a neighboring PSW biased with a constant voltage. It is found that, under the influence of the biased neighboring PSW, the sensing channel currents of the PSW with γ -APTES sensing film are much lower than those of the PSW sensor with γ -APTES + NPs + UV sensing film, while the channel current deviation errors of the PSW with γ -APTES sensing film are much higher than those with γ -APTES + NPs + UV sensing film. These improvements are ascribed to the smaller surface leakage current and superior molecular structure of the γ -APTES + NPs + UV sensing film. Apparently, the γ -APTES + NPs + UV sensing film is a better choice for PSW array sensors.